Bathiymetric distribution of Pleuromamma (Copepoda, Calanoida) species in the Indian Ocean - Jayalakshmi, K V (Indian Journal of Fisheries, 2011)
Based on ihe analysis of 204 zooplankton samples from the stratified depths in the Indian ocean collected during the International Indian Ocean Expedition (IIOE), the distribution of the genus Pleuromamma, a Calanoid Copepod, was studied. Seven species, viz. Pleuromamma indica, P. gracilis P. piseki, P. abdominalis, P. borealis, P. xipias and P. quadrungulala, in the order of their abundance, and 1 variety of the genus P. abdominalis abyssal is were observed. Vertical distribution of species of Pleuromamma showed that they were inversely correlated with depth. Among the Pleuromamma species, P. indica could survive in an environment of low dissolved oxygen and lower depths of water column, whereas P. xipias and P. abdominalis could survive in an environment of high dissolved oxygen and at almost all depths of water column. Multiple regression analysis of the data suggested that light intensity, further depth stratification, seasonal variations, water currents and the interaction effects of temperature with dissolved oxygen and nutrients could provide a more pronounced prediction of the total abundance of the Pleuromamma species. Diversity function H (s), in relation to latitude was a bell-stuped normal curve. HO) was linearly related to evenness index, e, and was a perfectly sloping up line. These relations were highly pronounced at lower depths of water column and in the highly productive regions.